2004
DOI: 10.1103/physrevlett.92.126101
|View full text |Cite
|
Sign up to set email alerts
|

Superlubricity of Graphite

Abstract: Using a home-built frictional force microscope that is able to detect forces in three dimensions with a lateral force resolution down to 15 pN, we have studied the energy dissipation between a tungsten tip sliding over a graphite surface in dry contact. By measuring atomic-scale friction as a function of the rotational angle between two contacting bodies, we show that the origin of the ultralow friction of graphite lies in the incommensurability between rotated graphite layers, an effect proposed under the nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

79
962
4
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,283 publications
(1,049 citation statements)
references
References 23 publications
79
962
4
4
Order By: Relevance
“…Superlow friction would subsequently be achieved because of the extremely weak interaction and easily sliding between the transferred GNFs and graphite in the incommensurate contact 6, 7, 10, 19. According to the previous studies on the superlubricity of graphite, the superlow friction would disappear at two certain sliding orientations with an angle difference of 60° under small loads 6, 7. However, we did not observe this sliding orientation dependency of the superlubricity under the high contact pressure.…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…Superlow friction would subsequently be achieved because of the extremely weak interaction and easily sliding between the transferred GNFs and graphite in the incommensurate contact 6, 7, 10, 19. According to the previous studies on the superlubricity of graphite, the superlow friction would disappear at two certain sliding orientations with an angle difference of 60° under small loads 6, 7. However, we did not observe this sliding orientation dependency of the superlubricity under the high contact pressure.…”
Section: Resultscontrasting
confidence: 62%
“…In this case, the GNFs may form the incommensurate sliding with the original graphite substrate because of their similar lattices. Superlow friction would subsequently be achieved because of the extremely weak interaction and easily sliding between the transferred GNFs and graphite in the incommensurate contact 6, 7, 10, 19. According to the previous studies on the superlubricity of graphite, the superlow friction would disappear at two certain sliding orientations with an angle difference of 60° under small loads 6, 7.…”
Section: Resultsmentioning
confidence: 97%
“…This would amount to the slider "ironing" the kinks onward. Dienwiebel et al [3] demonstrated how incommensurability may lead to virtually friction-free sliding in such a case, but no measure was obtained for the flake relative sliding velocity. Real substrates are, unlike our model, not rigid, subject to thermal expansion, etc.…”
Section: Discussionmentioning
confidence: 99%
“…6 Super-diffusivity has been observed in systems involving graphitic compounds: fullerenes, 7,8 metallic clusters 9 or graphene flakes adsorbed on graphite. 10,11 The existence of quadrupole or higher order interactions may cause the super-diffusivity between graphene and graphite observed with atomic force microscopy (AFM). 10,12,13 Interactions of the same nature exist in poly-aromatic hydrocarbons (PAH) adsorbed on graphitic substrates, 14,15 which are characterized by a very low energy barrier for lateral diffusion 16 and can act as nano-sized lubricants.…”
mentioning
confidence: 99%